La Música del Mariachi: Conservator of Mexican Culture and Heritage - Rachel Yvonne Cruz (Estudios Humanísticos. Filología, 2023)
Mariachi music, its profound texts, rhythms, and mestizaje (racial mixture) preserve Mexican culture and heritage. Mariachi music is synonymous with Mexico. Both birthed through a violent beginning of forced assimilation and mestizaje, mariachi is one of the foremost symbols of Mexican national pride. Mariachi’s lyrics and distinctive rhythms, share and preserve a story of survival, cradle ancestral epistemologies, all that is Mexico, its Indigenous, Spanish, and African roots and history pre and post 1821. And just as in the study of any other music, language, or culture, it is consequential that precise, literal, translations (scores) of mariachi music, research, and other scholarly, cultivated resources are accessible to all Mexican descent people, especially Chicana/x/o students and those who teach them. Culturally relevant curriculum fosters identity and inclusivity and promotes academic success. However, as it pertains to music education, western European music history, theory, notation, and praxes dominate. With over 62 million Hispanics living in the United States, 62% of Mexican descent, it is dire to create decolonized music spaces that offer more than a single narrative. And within these spaces, it is crucial that quality resources are provided equitably. Because of its popularity and adoption as core curriculum in schools around the United States, amassing quality mariachi educational resources, musical scores and transcriptions, and other curricular materials is central to Mexican descent student success. In this article, I describe common mariachi song forms, their region of origin, meter, text structure and offer rhythmic analyses and examples for notating them.